Pendampingan Budidaya Maggot Lalat Black Soldier Fly Sebagai Pengembangan Potensi Lokal Masyarakat: Black Soldier Fly Maggot Cultivation Assistance as Development of Local Community Potential - Yuwita, Nurma; Hasyim, Mochamad; Asfahani, Asfahani (LP2M INSURI Ponorogo, 2022)
This service aims to empower and explore the potential of Sebandung Village residents in processing organic waste into maggot Black Soldier Fly. The service method used is Community Based Research which is carried out with the community to overcome problems. The service implementation is done through socialization, training, media creation, and the Black Soldier Fly maggot cultivation guidebook. The community is very active and enthusiastic in participating in the education of Black Soldier Fly maggot cultivation from the socialization to the end of the Black Soldier Fly maggot cultivation demonstration. The conclusion is that the maggot cultivation activity in Sebandung village was successful and maximal with indicators of increasing the education and skills of the participants. It is hoped that this service activity will become a milestone for organic waste processing in various villages in the Pasuruan district.